Orthopedic Surgery Residents’ Perception of Online Education in Their Programs During the Covid-19 Pandemic: Should It Be Maintained After the Crisis? - Medina-Figueroa, N (Taylor and Francis Ltd., 2020)
Background and purpose — During the COVID-19 pandemic, most of the teaching centers in Chile have shifted to online resources. We decided to do a survey on orthopedic residents regarding this type of education to assess for strengths and weaknesses of digital education in orthopedic programs. Methods — A survey was performed targeting 110 orthopedic residents belonging to different training programs around the country. 100 residents completed the survey. Results — 86% stated that their programs are using online education. When asked in detail, 86% had been involved in webinars, 28% had received online presentations, 12% had participated in online tests, and 7% had evaluated patients. Webinars were rated (1 = very unsatisfactory, 10 = very satisfactory) with a mean grade of 8.1 (1–10), online presentations 7.3 (1–10), online tests 3.8 (1–8), and online patient evaluations 2.9 (1–9). When asked if, after the end of the pandemic, they would continue using the online modalities, 82% would continue attending webinars, 72% would continue watching online presentations, 27% would continue performing online tests, and 33% of the residents would continue performing online evaluations of patients. Interpretation — Even though resident evaluation of online activities is positive, face-to-face theoretical activities are still valued as a necessary complement for orthopedic residency education. © 2020 The Author(s). Published by Taylor & Francis on behalf of the Nordic Orthopedic Federation.